2022
DOI: 10.1021/acs.jmedchem.2c00877
|View full text |Cite
|
Sign up to set email alerts
|

Linker-Dependent Folding Rationalizes PROTAC Cell Permeability

Abstract: Proteolysis-targeting chimeras (PROTACs) must be cell permeable to reach their target proteins. This is challenging as the bivalent structure of PROTACs puts them in chemical space at, or beyond, the outer limits of oral druggable space. We used NMR spectroscopy and molecular dynamics (MD) simulations independently to gain insights into the origin of the differences in cell permeability displayed by three flexible cereblon PROTACs having closely related structures. Both methods revealed that the propensity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 57 publications
1
47
1
Order By: Relevance
“…Recent studies have revealed that the propensity of PROTACs to adopt folded, non-polar conformations in an apolar environment correlates to high cell permeability. 17,18 We conclude that BCMs can be implemented to support decision-making in drug discovery projects so that PROTACs predicted to have high permeability are prioritized for synthesis and subsequent testing over those predicted to have low permeability. Such classification models could be of particular value for prioritization of compounds early in lead optimization before large numbers of PROTACs have been synthesized in the project.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Recent studies have revealed that the propensity of PROTACs to adopt folded, non-polar conformations in an apolar environment correlates to high cell permeability. 17,18 We conclude that BCMs can be implemented to support decision-making in drug discovery projects so that PROTACs predicted to have high permeability are prioritized for synthesis and subsequent testing over those predicted to have low permeability. Such classification models could be of particular value for prioritization of compounds early in lead optimization before large numbers of PROTACs have been synthesized in the project.…”
Section: Discussionmentioning
confidence: 98%
“…One reason for this complex behavior may be the 3D folding of PROTACs. Recent studies have revealed that the propensity of PROTACs to adopt folded, non-polar conformations in an apolar environment correlates to high cell permeability. , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even TPD provided a promising potential to access undruggable protein degradation, but still, in general, the lack of discrimination between healthy cells and cancer cells could raise the issue of off-target toxicities. Additionally, their physicochemical characteristics are associated with generally poor DMPK properties and low bioavailability. Therefore, as a drug delivery concept, antibody conjugates provide emerging strategies for the TPD area. Using antibody conjugates, degraders can be delivered specifically to the targeted cancer-associated cells.…”
Section: Introductionmentioning
confidence: 99%